2018
DOI: 10.1007/s00109-018-1647-4
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between cardiac transcription factors and non-coding RNAs in predisposing to atrial fibrillation

Abstract: There is growing evidence that putative gene regulatory networks including cardio-enriched transcription factors, such as PITX2, TBX5, ZFHX3, and SHOX2, and their effector/target genes along with downstream non-coding RNAs can play a potentially important role in the process of adaptive and maladaptive atrial rhythm remodeling. In turn, expression of atrial fibrillation-associated transcription factors is under the control of upstream regulatory non-coding RNAs. This review broadly explores gene regulatory mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 106 publications
(125 reference statements)
0
5
0
Order By: Relevance
“…Additionally, TCONS_00075467 adsorbed miR-328 to derepress the downstream target gene L-type voltage-dependent calcium channel subunit α1C expression to alleviate AF electrical remodeling. Several cardiac-specific transcription factors, such as paired-like homeodomain transcription factor 2 (PITX2) and T-Box transcription factor 5 (TBX5), have been shown to be involved in the regulation of ion channel genes and play a role in AF, with decreasing PITX2 level shortening atrial effective refractory period [ 34 , 35 ]. Gore-Panter et al identified a lncRNA gene localized upstream to the PITX2 gene, called PITX2 adjacent non-coding RNA (PANCR) [ 36 ].…”
Section: Lncrnas and Cardiac Electrical Remodelingmentioning
confidence: 99%
“…Additionally, TCONS_00075467 adsorbed miR-328 to derepress the downstream target gene L-type voltage-dependent calcium channel subunit α1C expression to alleviate AF electrical remodeling. Several cardiac-specific transcription factors, such as paired-like homeodomain transcription factor 2 (PITX2) and T-Box transcription factor 5 (TBX5), have been shown to be involved in the regulation of ion channel genes and play a role in AF, with decreasing PITX2 level shortening atrial effective refractory period [ 34 , 35 ]. Gore-Panter et al identified a lncRNA gene localized upstream to the PITX2 gene, called PITX2 adjacent non-coding RNA (PANCR) [ 36 ].…”
Section: Lncrnas and Cardiac Electrical Remodelingmentioning
confidence: 99%
“…A growing number of evidence suggests that putative gene regulatory networks (GRNs), including cardiac-enriched transcription factors (TFs) and its target genes, can play a potentially important role in the process of adaptive and maladaptive atrial rhythm remodeling (90)(91)(92). In addition, the human genome-wide association studies (GWAS) have successfully identified more than 100 genetic sites associated with atrial fibrillation, including genes encoding cardioenriched TFs (93,94).…”
Section: Transcription Factors (Tfs) and Ncrnamentioning
confidence: 99%
“…Further, genes related to structural abnormalities are regulated by mir-21, mir-26, mir-29b, mir-30, mir-133 and mir-590 45 . Perturbations of a dynamic expression balance between TFs, such as PITX2, TBX5, ZFHX3, and SHOX2, and corresponding miRNAs may predispose to AF 46 . The possibility of the complex interaction among circRNAs, miRNAs, and mRNAs is also proposed in AF patients 47 .…”
Section: Ncrnasmentioning
confidence: 99%